Investigation of resveratrol production by genetically engineered Saccharomyces cerevisiae strains - Trollope, Kim (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Wine Biotechnology))--University of Stellenbosch, 2006.